Case Report: A case of multisystem inflammatory syndrome in an 11-year-old female after COVID-19 inactivated vaccine - Saeed, Saboor; Cao, Jianqing; Xu, Jinjiao; Zhang, Yi; Zheng, Xuyang; Jiang, Liya; Jiang, Chunming; Zhang, Xinjuan (Frontiers in Pediatrics, 2023)
Abstract Background: Multisystem inflammatory syndrome in children (MIS-C), also known as pediatric inflammatory, multisystem syndrome temporally associated with SARS-CoV-2, is a rare but serious complication of SARS-CoV-2 infection in children that typically occurs 2-6 weeks after SARS-CoV-2 infection. The pathophysiology of MIS-C is unknown. MIS-C, first recognized in April 2020, is characterized by fever, systemic inflammation, and multi-system organ involvement. Post-vaccination adverse effects have increased with COVID-19 vaccinations, and MIS linked to immunization with COVID-19 vaccines has also been observed. Case Report: An 11-year-old Chinese girl presented with a high-grade fever, rash, and dry cough for 2 days. She had her 2nd SARS-CoV-2 inactivated vaccination dose five days before hospital admission. On day 3, she experienced bilateral conjunctivitis, hypotension (66/47 mmHg), and a high CRP level. She was diagnosed with MIS-C. The patient's condition deteriorated rapidly, necessitating intensive care unit admission. The patient's symptoms improved after intravenous immunoglobulin, methylprednisolone, and oral aspirin therapy. She was discharged from the hospital after 16 days as her general condition, and laboratory biomarkers returned to normal. Conclusion: Inactivated Covid-19 vaccination might trigger MIS-CFurther research is needed to evaluate whether a correlation exists between COVID-19 vaccination and MIS-C development.